A Study on Child Rearing Attitude of Working Mothers - Sinha, Rekha; Kumari, Kavita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Parents are increasingly encouraged to engage in positive reinforcement, open communication, and mutual respect rather than using fear or coercion. This change reflects broader socio-cultural changes including education reform, child rights advocacy, psychological research, and the influence of global parenting philosophies. The child is now viewed not as a passive recipient of instruction but as an individual with rights, opinions, and potential. This modern view of parenting requires time, effort, empathy, and adaptability, qualities that are often shaped by the parents’ own upbringing, personality, and life circumstances. A critical factor influencing child-rearing attitudes is the mother’s employment status. The distinction between working and non-working mothers introduces variations in time availability, stress levels, economic security, and emotional presence.